Understanding the effects of COVID-19 on P-12 teachers: a review of scholarly research and media coverage - LaTronica-Herb, Alexandra; Karalis Noel, Tiffany (Frontiers in Education, 2023)
This qualitative content analysis explores the multi-dimensional challenges faced by P-12 teachers amid the seismic shifts caused by the COVID-19 pandemic. Analyzing 49 academic literature and news reports from 2020 to 2022, the study identifies personal and professional stressors experienced by teachers. Personal factors, such as diminished self-efficacy, work-life balance issues, health and safety concerns, and secondary trauma, emerged as significant stressors during the pandemic. Additionally, professional factors, including heightened workload, ambiguous responsibilities, and inadequate support, have contributed to increased burnout and contemplation of leaving the profession. Strategic interventions proposed to address these issues include enhanced administrative support, increased professional agency, stress reduction measures, promotion of work-life balance, and technical training opportunities. The study calls for renewed societal respect for the teaching profession and ongoing research into the evolving needs and challenges of educators, especially in underserved communities. The aim is to provide valuable insights and potential solutions to support teachers during and beyond the pandemic, ultimately benefiting both educators and students as they navigate the changing landscape of education.